(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This study aimed to describe the art’s development in Cirebon Regency in 1966-2000. Ultimately examined the development of Tarling art’s function in Cirebon Regency in 1966-2000. To discuss this problem, the authors conducted a study using the historical method which consisting of four steps: heuristics, source criticism, interpretation, and historiography. Based on the findings, there are three functions in Tarling’s art performance. Firstly, Tarling functioned as a medium of entertainment for local communities that accompanying them to stay awake at night while burning bricks, harvest parties, and celebratory events. As an educational medium, there are values and morals incorporated in dramas and Tarling song lyrics that presented. As a communication medium, Tarling is often performed using regional languages to reach out to villagers who are still illiterate. Therefore, it is used as a communication medium by the government to deliver development messages. These three functions, made Tarling’s art possess its uniqueness as the character and identity of the Cirebon’s society, thus must be preserved.